Comunalidade na liquidez: características, determinantes e implicações no mercado acionário brasileiro - Silva Júnior, Claúdio Pilar da (2017)
This thesis aimed at analyzing the characteristics, determinants and implications of communality in liquidity for the Brazilian stock market. The analyzed sample consisted of, on average, 130 shares per year, of the companies listed on the São Paulo Stock Exchange - BM&FBOVESPA, from January 2007 to December 2015. Initially, it was sought to investigate the existence of commonality in Liquidity in the Brazilian stock market and to identify the economic-financial characteristics of the companies that made up the sample. With the use of financial volume as a measure of share liquidity, it was verified that commonality is a phenomenon present in the Brazilian stock market and that its highest values were concentrated in periods of international financial crises. In addition, it was verified the existence of a size effect on the commonality, that is, as the size of the company increases, a greater commonality in the liquidity is observed. Next, it was sought to analyze the determinants of commonality in liquidity, based on explanations on the supply side. It has been found that past commonality exerts a positive influence on the concomitant commonality. In addition, the negative influence of the market return and the positive influence of market volatility on the commonality in liquidity, showed that the commonality may be greater in periods of crisis due to capital restriction, however, it was verified that crises and the loss of Brazil's investment grade were not significant in explaining the commonality. In addition, it was sought to verify the influence of the foreign investor on the commonality with the use of five variables. The results showed that the participation of the foreign investor, measured by foreign purchases (CE) and foreign exchange participation (PECB), is significant to reduce the commonality in liquidity and that the output of foreign resources influences directly the increase of commonality. Finally, with the use of portfolios, it was sought to verify if the investors were compensated for dealing with the commonality. A premium of 0.33% per month for liquidity commonality was observed, however, not statistically significant. Regarding the risk factors analyzed, there was a market premium of 0.3% per month, but not significant. In relation to the size factor and the B/M factor, the results obtained disqualify the effect size and the effect value in the Brazilian stock market, since there was a negative premium for the risk factors of 0.005% and 2.516% per month, respectively. As for the moment factor, a monthly premium of 1.24% was obtained, significant at the 5% level. The liquidity factor presented a positive premium, but not statistically significant. Additionally, it was verified that when exposing the premium for commonality to the other risk factors, the market risk factor can capture it. Finally, it was found that commonality in liquidity is a priceless risk factor.